British Association of Dermatologists' guidelines for the management of Stevens–Johnson syndrome/toxic epidermal necrolysis in children and young people, 2018. (25th April 2019) - McPherson, T.; Exton, L.S.; Biswas, S.; Creamer, D.; Dziewulski, P.; Newell, L.; Tabor, K.L.; Wali, G.N.; Walker, G.; Walker, R.; Walker, S.; Young, A.E.; et al.
Abstract : Linked Comment: Lee. Br J Dermatol 2019; 181 :10–11 . Plain language summary available online